(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2025)
Background: Congenital Heart Disease (CHD) is a prenatal heart abnormality. Dermatoglyphics, an epidermal ridge on the palmar surface of the hand, develops early in pregnancy and may be inherited or environmental. Skin and cardiac development during pregnancy are associated with congenital heart disease. Palmar dermatoglyphic patterns can be utilized as a screening test for suspected CHD patients to prevent additional complications. Thus, this study aimed analysis of CHD patients’ palmar dermatoglyphic patterns. Materials and methods: The Department of Anatomy, Chittagong Medical College, Chattogram, carried out this cross-sectional observational study on 130 pediatric cardiology patients from January 2022 to January 2023. A Chi-square test was used for statistical analysis, with a pvalue of <0.05 considered significant with 95% confidence. Results: CHD patients had significantly decreased finger arch pattern frequency compared to the control group (p< 0.001). CHD had more ulnar loop and whorl patterns than the control group, but the differences were not statistically significant (p > 0.05). Conclusion: CHD patients have distinct palmar dermatoglyphics than non-CHD patients. Dermatoglyphic screening can detect suspected CHD patients in remote places and avoid consequences. JCMCTA 2023 ; 34 (2) : 42-45